Effects of Preventing Alcohol Consumption Program by Applying Self-Efficacy Theory on Avoiding Alcohol Consupmtion of Lower Secondury School Students - Intapan, Jutamas; Wattanburanon, Aimutcha; Chotigawin, Rotruedee; Isarankura Na Ayudhaya, Walai (Journal of The Royal Thai Army Nurses, 2021)
This quasi-experimental research aimed to study the alcohol drinking prevention program applying self-efficacy theory among secondary school students. The 66 samples were divided by the purposive sampling method into two groups: 33 experimental group and 33 comparison group. The experimental instrument were 1.) The alcohol drinking prevention program applying self-efficacy theory learning management plans. 2.) The self-efficacy questionnaire 3.) The alcohol drinking prevention questionnaire 4.) The alcohol knowledge test. The data obtained were analyzed by using percentage, frequency, standard deviation, t-test, One-way ANOVA, LSD and it conducted the level of statistical significance at .05 level. The findings were as follows: 1.) After treatment, the mean scores of the self-efficacy, the mean scores of alcohol drinking prevention behavior and the mean scores of alcohol knowledge test from the alcohol drinking prevention program of the experimental group were found higher than the comparison group in statistically significant at .05 level. 2.) After treatment, the mean scores of the self-efficacy, the mean score of alcohol drinking prevention behavior and the mean scores of alcohol knowledge test from the alcohol drinking prevention program of the experimental group were found higher than before treatment in statistically significant at .05 level. While the follow-up phase and after treatment were found no different.